The genes for secretion and maturation of lactococcins are located on the chromosome of Lactococcus lactis IL1403. - Venema, K (1996)
Southern hybridization and PCR analysis were used to show that Lactococcus lactis IL1403, a plasmid-free strain that does not produce bacteriocin, contains genes on its chromosome that are highly homologous to lcnC and lcnD and encode the lactococcin secretion and maturation system. The lcnC and lcnD homologs on the chromosome of IL1403 were interrupted independently by Campbell-type integrations. Both insertion mutants were unable to secrete active lactococcin. Part of the chromosomal lcnC gene was cloned and sequenced. Only a few nucleotide substitutions occurred, compared with the plasmid-encoded lcnC gene, and these did not lead to changes in the deduced amino acid sequence. No genes homologous to those for lactococcin A, B, or M could be detected in IL1403, and the strain does not produce bacteriocin activity.